Tantangan dan Peluang Penerapan Standar Akuntansi Keuangan di UMKM - Agnes Lamtio; Putri Adellia; Febianti Az-Azahra; Dhea Angelita (J-Coop : Journal of Co-operative, 2026)
This study aims to examine the challenges and opportunities in the implementation of Financial Accounting Standards, particularly SAK EMKM, in Micro, Small, and Medium Enterprises (MSMEs) and cooperatives. The research focuses on identifying key obstacles faced by MSMEs and cooperatives in applying standardized financial reporting, as well as exploring the potential benefits arising from the adoption of these standards. This study employs a qualitative descriptive method through a literature review of relevant academic journals, regulations, and previous empirical studies related to the application of financial accounting standards in MSMEs and cooperatives. The findings indicate that the main challenges in implementing SAK EMKM include limited accounting knowledge, low awareness of financial reporting standards, and inadequate technological resources. On the other hand, the application of financial accounting standards presents significant opportunities, such as improving the quality and transparency of financial statements, enhancing accountability, facilitating access to external financing, and supporting more informed decision-making processes. In conclusion, despite the existing challenges, the implementation of financial accounting standards in MSMEs and cooperatives has strong potential to promote sustainable business growth, provided that continuous training, assistance, and institutional support are strengthened.